Hilirisasi Kegiatan Penggalian dan Pengangkutan pada Penambangan Batu Kapur di PT. Semen Padang - Intan Maharani Besri; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Semen Padang, which was established in 1990, is a state-owned company (BUMN) which is a national cement producer for the needs of the domestic market. PT Semen Padang uses the open pit mining method with a quarry mining system which includes land clearing, material unloading by blasting, loading, transporting and processing materials. to dismantle hard rock is usually done by blasting. The resulting blasting vibration must be in a safe condition for the surroundings. The reality on the ground is that blasting often creates impacts and complaints for the communities around the mine. The purpose of this paper is to find the results of the blasting fractionation produced by loading hauling and about the environment around the mine. The location of this research was carried out in the Karang Putih area of PT.Semen Padang, Padang City, West Sumatra Province in November 2019. From the blasting activity, the size of the rock fragmentation resulted from the blasting was small from 80 cm, only 53.218%,From loading and hauling activities, the Hitachi EX 2500-6 (EH06) excavator productivity is 805.47 tons / hour, the Komatsu 785-7 Heavy Dumptruck is 203.177 tons / hour, the required Heavy Dumptruck is 4 units, and the work compatibility of the tools is 0.807. , Crusher VI productivity is 2128,761 tonnes / hour and the total production in December 2019 is 10218.0545 tonnes / month. water pollution control, Air Pollution Control, Noise Level Quality Standards, Vibration Level Quality Standards. Keywords: fragmentation, productivity, production, limestone, environment